Pelatihan Pencatatan Transaksi dan Etika Keuangan untuk Meningkatkan Tata Kelola Kedai Kopi - Gloria Alexander; Felicia Edlyn Tetimau; Agnes Natalia Dequelju; Theressia Sellanova; Mariana Ing Malelak (Universitas Negeri Gorontalo, 2025)
Internal fraud such as cash theft and unauthorized use of raw materials has become a serious issue at a coffee shop in Surabaya, especially amid declining customer numbers and business income. This situation highlights the need for intervention to improve overall financial and operational management. This community service project aims to enhance transparency and accountability through transaction recording training, financial ethics education, implementation of a Point of Sale (POS) system, simple internal audits, and regular cash inspections. The method involved observation, interviews, document analysis, training sessions, and online mentoring conducted from February to March 2025. The results showed improved employee understanding of accurate record-keeping, a significant decrease in daily cash discrepancies, and the development of more responsible work habits. In conclusion, a structured financial and operational system can reduce the risk of fraud and support the long-term sustainability of the business.